PENDAMPINGAN PENGGUNAAN MAINAN WIPE AND CLEAN DAN VIDEO SEBAGAI MEDIA EDUKASI UNTUK MENINGKATKAN PENGETAHUAN PASIEN ANAK TENTANG CARA MENYIKAT GIGI YANG BAIK DAN BENAR - Andina Muzayyanti (Najah: Journal of Research and Community Service, 2023)
The use of effective educational media is essential in improving knowledge acquisition, especially among young patients. This community engagement project aims to support the implementation of educational tools, specifically "Wipe and Clean" toys and instructional videos, to increase pediatric patients' awareness of proper dental hygiene. The initiative involved hands-on guidance in using the toys and videos to demonstrate proper brushing techniques. A comprehensive approach was taken, including interactive sessions, practical demonstrations, and informative discussions. Initial results showed a marked improvement in children's understanding of proper brushing methods. This project highlights the potential of innovative educational tools in instilling important oral care practices for young patients, thereby contributing to their overall oral health and well-being.